(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article analyzes the relevance of the pharmacovigilance system in modern conditions, its role in ensuring the safety of medicines, and its practical mechanisms. In recent years, the expansion of the range of medicines, the increase in the share of biological drugs and generics, as well as the increase in self-medication among the population, create the need to further improve the pharmacovigilance system. The article comparatively highlights the effectiveness of the processes of identifying, registering and analyzing adverse reactions. It also considers the issues of sustainable control of the safety profile of medicines, protecting patient health, and strengthening trust in the healthcare system through strengthening pharmacovigilance on a scientific basis.